Giải pháp nhằm thúc đẩy tăng trưởng kinh tế và phát triển bền vững trong kỷ nguyên mới - Nguyễn Đông, Phong (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This article proposes strategic solutions to promote economic growth and sustainable development for Vietnam in the 2025–2030 period, aiming to become a high-income country by 2045. The focus is on promoting science and technology, innovation, and digital transformation to create new growth drivers; overcoming the middle-income trap through education reform, improving labor productivity, and developing a social welfare system adapted to an aging population. At the same time, the article emphasizes the importance of selecting sectors with comparative advantages (such as processed manufacturing, tourism, green construction, high-tech agriculture, and logistics) for prioritized investment. Besides, it advocates for regional development and inter-regional linkages through infrastructure investment, decentralization, building specialized industry clusters, and shared data. The proposed solutions are drawn from scientific research results and a national seminar organized by the University of Economics Ho Chi Minh City, contributing to shaping effective and sustainable development policies in the new era.